High-entropy molybdenum-based oxide and preparation method and application thereof

By using high-entropy molybdenum-based oxide as amorphous working electrode in electrolytic water hydrogen production technology and using glycerol electrooxidation reaction instead of the OER process, the efficiency reduction caused by overpotential in electrolytic water hydrogen production technology is solved, and the effect of efficient hydrogen production and electrochemical value-added glycerol is achieved.

CN119911983APending Publication Date: 2025-05-02SHANDONG NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510129899.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, excessive overpotentiality leads to slow oxygen evolution reaction (OER) in the key steps of hydrogen fuel production in the water decomposition system, reducing the overall efficiency of water decomposition.

Method used

High-entropy molybdenum-based oxide is used as the amorphous working electrode, and the OER process in electrolytic water is replaced by glycerol electrooxidation reaction, and the rich active sites of high-entropy molybdenum-based oxide and the rapid reaction kinetics of glycerol are used to improve the working efficiency of electrolytic water.

Benefits of technology

The efficient hydrogen production of electrolytic water is achieved, the working efficiency of electrolytic water is improved, and a variety of value-added chemical products are generated through electrooxidation of glycerol, such as formic acid, glyceric acid, etc., thus achieving electrochemical value-added glycerol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911983A_ABST
    Figure CN119911983A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolyzed water, and particularly relates to a high-entropy molybdenum-based oxide and a preparation method and application thereof.The chemical general formula of the high-entropy molybdenum-based oxide is MFeMoOx, x is larger than or equal to 2 and smaller than or equal to 4, M is any three or more elements of V, Cr, Mn, Co, Ni and Cu, the total molar ratio of M to Fe is the same as the molar ratio of Mo, the molar ratios of all elements in M are the same, and the total molar ratio of M to Fe is larger than or equal to 2 and smaller than or equal to 4. And the high-entropy molybdenum-based oxide is of an amorphous structure. The amorphous state of the high-entropy molybdenum-based oxide can provide abundant and relatively uniformly distributed active sites, so that the electrochemical reaction is efficiently carried out, and the prepared electrode is high in activity and good in conductivity; glycerol is used as an electrolyte, the current density is stable, the performance is stable, and meanwhile, the glycerol can generate various value-added chemical products such as formic acid and glyceric acid through electrooxidation, so that the electrochemical value-added effect of the glycerol can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water electrolysis, and specifically relates to a high-entropy molybdenum-based oxide and a preparation method and application thereof. Background Art

[0002] As a renewable energy, hydrogen energy has become the primary new energy source in energy transformation due to its advantages of green and sustainable development. Among the current hydrogen production technologies, water electrolysis hydrogen production technology meets the requirements of environmental protection and sustainable development, and has the advantages of low pollution, high efficiency, low cost, and renewability, making it an ideal way to produce hydrogen. However, due to the high overpotential, the four-electron transfer process in the oxygen evolution reaction (OER), a key step in the production of hydrogen fuel in the water splitting system, is slow, which reduces the overall efficiency of water splitting.

[0003] High entropy materials (HEMs) are formed by five or more metal elements, have tunable multi-metal active centers, and are highly disordered in structure and have random arrangement of metal elements. They have attracted widespread attention due to their unique structure and electrochemical properties to be explored.

[0004] As a byproduct of the fast-growing biodiesel industry, glycerol has become a cheap and over-capacity biomass-derived chemical product. Traditional glycerol utilization is relatively limited, mainly used in industries such as cosmetics and food, which cannot fully consume the large amount of glycerol produced.

[0005] In the prior art, patent application number 202310889224.1 discloses a nickel sulfide / nickel oxide electrode and its preparation method and application. Although the prepared nickel sulfide / oxide electrode can efficiently oxidize small molecules of biomass-derived alcohols such as ethanol, glycerol, and glucose into high-value products, thereby achieving efficient value-added of biomass derivatives, its activity, selectivity, and stability are still difficult to meet industrial needs. Summary of the invention

[0006] Terminology explanation:

[0007] Glycerol electrochemical value-added: Glycerol electrochemical value-added refers to the conversion of glycerol into chemicals with higher economic value through electrochemical methods. Glycerol is the main by-product in the production of biodiesel and has limited value itself. However, through electrochemical means, glycerol can be converted into a variety of high value-added organic compounds such as dihydroxyacetone, glyceric acid, lactic acid, etc.

[0008] Partial oxidation reaction of glycerol: C3H8O3+14OH - -14e-=3CO3 2- +11H2O

[0009] High-entropy materials: High-entropy materials are multi-component materials, usually composed of five or more main elements. Due to the mixture of multiple elements, high-entropy materials have multiple oxidation states and electronic states, which enables high-entropy materials to exhibit good electronic conductivity in OER, and make high-entropy materials have abundant surface defects and vacancies, thereby exposing more active sites, which also provides great possibilities for adjusting the microstructure and maximizing OER activity.

[0010] The purpose of the present invention is to provide a high-entropy molybdenum-based oxide and a preparation method and application thereof, so as to overcome the shortcomings of the prior art. The amorphous state of the high-entropy molybdenum-based oxide can provide abundant and relatively evenly distributed active sites, ensuring that the electrochemical reaction is carried out efficiently; using glycerol as the electrolyte, the current density is stable, the performance is stable, and at the same time, glycerol can be electro-oxidized to generate a variety of value-added chemical products, such as formic acid, glyceric acid, etc., to achieve electrochemical value-added of glycerol.

[0011] In order to achieve the above object, the technical solution of the present invention is:

[0012] In a first aspect, the present invention provides a high entropy molybdenum-based oxide, wherein the chemical formula of the high entropy molybdenum-based oxide is MFeMoO x , wherein 2≤x≤4, M is any three or more elements of V, Cr, Mn, Co, Ni and Cu, the total molar ratio of M to Fe is the same as the molar ratio of Mo, the molar ratio of each element in M ​​is the same, and the high entropy molybdenum-based oxide is an amorphous structure.

[0013] In some other embodiments, the M is any three of V, Cr, Mn, Co, Ni and Cu.

[0014] In some other embodiments, the high entropy molybdenum-based oxide is FeCoNiCuMoO x 、FeCoVCuMoO x 、FeCoNiZnMoO x and FeMnNiCuMoO x One of the following, where 2≤x≤4;

[0015] Preferably, the molar ratio of Fe to any three elements of V, Cr, Mn, Co, Ni and Cu in M ​​is 1:2:2:2.

[0016] The inventors found during the research that in molybdenum-based oxides, common oxidation states of molybdenum are +2, +4, +6, etc. When the number of oxygen atoms is selected (2≤x≤4), in order to make the high-entropy molybdenum-based oxide reach an ideal state in terms of specific electronic structure, chemical stability and reactivity; from the perspective of redox, such a range of oxygen atoms can ensure that the molybdenum element forms a suitable chemical bond with other metal elements to meet the functional requirements of the material.

[0017] One of the characteristics of high entropy alloys or high entropy compounds is that multiple elements exist in equal or approximately equal molar ratios, which can give the system a high entropy effect. The total metal molar ratio in M ​​is the same as the molar ratio of Mo, which can ensure the high entropy characteristics of the system, and thus may bring properties different from those of traditional single or a few element compounds, such as enhanced hardness, corrosion resistance, catalytic activity, etc. From the perspective of crystal structure, this equimolar ratio design helps to form a more uniform structure and avoid problems such as phase separation caused by differences in element ratios.

[0018] The molar ratio of Fe to any three elements of V, Cr, Mn, Co, Ni and Cu in M ​​is 1:2:2:2, and the effect is better when the Fe content is low. This is because the high entropy effect can increase the mixing entropy of the system, making it difficult for the system to form an ordered crystal structure during solidification or synthesis. The interaction of multiple metal elements with molybdenum and oxygen increases the complexity of atomic arrangement, and the interaction between atoms becomes more diverse, which inhibits the nucleation and growth process of the crystal, and thus tends to form an amorphous structure.

[0019] In a second aspect, the present invention provides a method for preparing the high entropy molybdenum-based oxide described in the first aspect, comprising the following steps: (1) adding an M metal salt, an iron salt and citric acid to a solvent to form a mixed solution; adding a molybdenum salt aqueous solution to the mixed solution to form a precursor solution;

[0020] (2) After the carrier is mixed with the precursor solution, it is sealed and subjected to a hydrothermal reaction to obtain a carrier loaded with a high-entropy molybdenum-based oxide.

[0021] In some other embodiments, in step (1), the M metal salt is any three or more of soluble salts of V, Cr, Mn, Co, Ni and Cu;

[0022] The iron salt is one of ferric nitrate, ferric sulfate and ferric chloride;

[0023] The total molar ratio of the iron salt and the M metal salt to the molar ratio of citric acid is (0.5-1.0): (1.0-2.0);

[0024] The solvent is a mixed solution of water and ethanol;

[0025] The mixing mass ratio of water to ethanol is 1:(1-3);

[0026] The concentration of the citric acid is 0.05-0.1 mol·L -1 .

[0027] In some other embodiments, in step (1), the molybdenum salt is one or more of Na2MoO4·2H2O, molybdenum nitrate, molybdenum chloride and molybdenum sulfate;

[0028] The concentration of the molybdenum salt aqueous solution is 0.04-0.06 mol·L -1 .

[0029] In some other embodiments, in step (2), the carrier is one of carbon cloth, carbon fiber, foam copper, stainless steel mesh and foam nickel;

[0030] The temperature of the hydrothermal reaction is 140-160° C. and the time is 20-25 hours.

[0031] In a third aspect, the present invention provides the use of the high entropy molybdenum-based oxide described in the first aspect in glycerol electro-oxidation, wherein the concentration of glycerol in the glycerol electro-oxidation is 0.05-0.15 mol·L -1 .

[0032] In a fourth aspect, the present invention provides a method for electrochemical valorization of glycerol, using the high entropy molybdenum-based oxide described in the first aspect as a working electrode, a platinum electrode as a counter electrode, a Hg / HgO electrode as a reference electrode, and KOH and glycerol as electrolytes for electro-oxidation.

[0033] In a fifth aspect, the present invention provides a composite electrode comprising a conductive substrate and the high entropy molybdenum-based oxide according to the first aspect supported on the surface of the conductive substrate.

[0034] The overall inventive concept adopted by the present invention is:

[0035] Metal molybdate compounds have good chemical stability and can maintain a relatively stable chemical structure in different electrolyte environments. Metal molybdate electrodes have good electrical conductivity. During the electrode reaction, electrons can be conducted relatively easily in the lattice of the molybdate compound, allowing the electrode reaction to proceed quickly. It also has good cycle stability, excellent electrochemical performance, low cost and environmental friendliness, so its amorphous state is used as a working electrode to improve the efficiency of water electrolysis.

[0036] Since the partial oxidation of glycerol not only has fast reaction kinetics and relatively low theoretical electrode potential, but also can selectively generate a variety of value-added chemical products such as glyceric acid, glycolic acid, and formic acid, replacing the anode OER in water splitting with the partial oxidation reaction of glycerol and then coupling it with the cathode HER can not only assist in the efficient production of hydrogen by water electrolysis, but also achieve the true value-added of glycerol.

[0037] Carbon cloth, carbon fiber, copper foam, stainless steel mesh and nickel foam substrate: have excellent conductivity, can provide efficient electron transmission channels for high entropy metal molybdates, reduce the resistance of the electrode, reduce energy loss during charging and discharging, and improve the reaction rate and electrochemical performance of the electrode.

[0038] The present invention creatively utilizes high-entropy molybdenum-based oxides to load on a carrier, and utilizes the amorphous state of the high-entropy molybdenum-based oxides to provide abundant and relatively evenly distributed active sites, thereby ensuring that the electrochemical reaction is carried out efficiently; using glycerol as the electrolyte, the current density is stable, the performance is stable, and at the same time, glycerol can generate a variety of value-added chemical products through electro-oxidation, thereby realizing the electrochemical value-added of glycerol.

[0039] Beneficial effects of the present invention:

[0040] (1) When the current density reaches 10 mA cm -2 When FeCoNiCuMoO x Potential is 1.23 V vs. RHE, FeCoVCuMoO x Potential is 1.30V vs.RHE, FeCoNiZnMoO x Potential is 1.36V vs.RHE, FeMnNiCuMoO x The potential is 1.38V vs. RHE, showing that the amorphous state of amorphous high entropy molybdate can provide abundant and relatively evenly distributed active sites, ensuring efficient electrochemical reactions; the electrodes made of amorphous high entropy molybdate and nickel foam have high activity and good conductivity.

[0041] (2) The oxidation reaction of small molecules such as glycerol can replace the OER process in water electrolysis, which can achieve efficient hydrogen production and improve the working efficiency of water electrolysis. Using glycerol as the electrolyte, the current density and performance are stable. At the same time, glycerol can be electro-oxidized to produce a variety of value-added chemical products, such as formic acid, glyceric acid, etc., thereby realizing the electrochemical value-added of glycerol. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0043] Figure 1 XRD spectra of Examples 1-4 of the present invention;

[0044] Figure 2 TEM and SEM of Example 1 of the present invention;

[0045] Figure 3 This is a property comparison diagram of embodiment 1 of the present invention in 0.1M glycerol (1M KOH) electrolyte and 1M KOH electrolyte;

[0046] Figure 4 LSV curves of embodiments 1-4 of the present invention in 1 M KOH and 0.1 M glycerol (1 M KOH) electrolyte. DETAILED DESCRIPTION

[0047] Those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Specific conditions are not specified in the examples, and the conventional conditions or conditions recommended by the manufacturer are used. The components used without indicating the manufacturer are all conventional products available on the market.

[0048] Instruments used in this experiment: X-ray diffraction (XRD) was performed on a Philips X'Pert Pro Super diffractometer, and the X-ray source was Cu Kα radiation. Scanning electron microscope images were taken on a JEOL JSM-6700F scanning electron microscope. Transmission electron microscope images were taken using a JEM-2100F field emission electron microscope at an accelerating voltage of 200 kV. High-resolution transmission electron microscopy (HRTEM), high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and corresponding elemental mapping analysis were performed on a ThermoFischer Talos F200X instrument. The atomic ratio of metals was determined on a Perkin Elmer Optima 7300DV inductively coupled plasma emission spectrometer (ICP-OES). X-ray photoelectron spectroscopy (XPS) analysis was performed using a VGESCALAB MKII X-ray photoelectron spectrometer with an excitation source of Mg Kα=1253.6 eV. The related products obtained from the glycerol electro-oxidation reaction were characterized by a nuclear magnetic resonance (NMR) spectrometer, and qualitative and quantitative analysis and calculation of related parameters were performed.

[0049] The invention provides a method for preparing a high-entropy molybdenum-based oxide, and uses a nickel foam loaded with the high-entropy molybdenum-based oxide as a working electrode to improve the working efficiency of water electrolysis.

[0050] 1. Preparation of high entropy molybdenum-based oxides

[0051] Before preparing nickel foam loaded with high entropy molybdenum-based oxide as a working electrode, the carrier (carbon cloth, carbon fiber, copper foam, stainless steel mesh or nickel foam) needs to be pretreated. The pretreatment method of the carrier is as follows: Place the carrier (1×4cm) in a beaker, add ethanol, and ultrasonicate for 5 minutes to remove organic matter on the surface of the carrier. Then, ultrasonicate with 1% dilute hydrochloric acid solution for 5 minutes to remove the surface oxide layer. Finally, wash with deionized water several times before using in subsequent experimental steps.

[0052] Example 1

[0053] (1)FeCoNiCuMoO x Synthesis of:

[0054] FeCoNiCuMoO was prepared by a one-step hydrothermal method. x, The specific preparation process is as follows:

[0055] 0.1 mmol of Fe(NO3)3·9H2O, 0.2 mmol of Co(NO3)2·6H2O, 0.2 mmol of Ni(NO3)2·6H2O, 0.2 mmol of Cu(NO3)2·3H2O and 1.5 mmol of citric acid were dissolved in 20 mL of a solution with a mass ratio of water to ethanol of 1:1, and ultrasonicated for 5 min to form solution A.

[0056] Then weigh 0.7 mmol of Na2MoO4·2H2O and dissolve it in 15 mL of deionized water, and ultrasonicate for 5 min to form solution B.

[0057] Solution B was slowly added to solution A to form a precursor solution, and ultrasonicated for 5 minutes. The treated nickel foam substrate was then placed in a 50 mL polytetrafluoroethylene liner, and the stirred precursor solution was then added to the liner and sealed. Then it was transferred to a stainless steel autoclave and kept at 160°C for 24 hours. Then it was naturally cooled to room temperature, and the nickel foam loaded with the catalyst was rinsed with deionized water and ethanol, and finally dried in a vacuum drying oven overnight.

[0058] (2) Using a typical three-electrode system, linear sweep voltammetry was performed on a Chenhua electrochemical workstation:

[0059] With FeCoNiCuMoO x The nickel foam substrate was used as the working electrode, the platinum electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and 1M KOH and 0.1M glycerol were used as the electrolyte. The test results showed that when the current density reached 10mAcm -2 When FeCoNiCuMoO x The potential was 1.23 V vs. RHE.

[0060] Example 2

[0061] (1)FeCoVCuMoO x Synthesis of:

[0062] FeCoVCuMoO was prepared by a one-step hydrothermal method. x The specific preparation process is as follows:

[0063] 0.1 mmol of Fe(NO3)3·9H2O, 0.2 mmol of Co(NO3)2·6H2O, 0.2 mmol of V(NO3)3·3H2O, 0.2 mmol of Cu(NO3)2·3H2O and 1.5 mmol of citric acid were dissolved in 20 mL of a solution with a mass ratio of water to ethanol of 1:1, and ultrasonicated for 5 min to form solution A.

[0064] Weigh 0.7 mmol of Na2MoO4·2H2O and dissolve it in 15 mL of deionized water. Ultrasonicate for 5 min to form solution B.

[0065] Solution B was slowly added to solution A to form a precursor solution, and ultrasonicated for 5 minutes. The treated copper foam substrate was then placed in a 50 mL polytetrafluoroethylene liner, and the stirred precursor solution was then added to the liner and sealed. Then it was transferred to a stainless steel autoclave and kept at 160°C for 24 hours. Then it was naturally cooled to room temperature, and the catalyst-loaded copper foam was rinsed with deionized water and ethanol, and finally dried in a vacuum drying oven overnight.

[0066] (2) A typical three-electrode system was used to perform linear sweep voltammetry tests on a Chenhua electrochemical workstation;

[0067] With FeCoVCuMoO x The foam copper substrate was used as the working electrode, the platinum electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and 1 M KOH and 0.1 M glycerol were used as the electrolyte. The test results showed that when the current density reached 10 mA cm -2 When FeCoVCuMoO x The potential was 1.30 V vs. RHE.

[0068] Example 3

[0069] (1)FeCoNiZnMoO x Synthesis of:

[0070] FeCoNiZnMoO was prepared by a one-step hydrothermal method. x The specific preparation process is as follows:

[0071] 0.1 mmol of Fe(NO3)3·9H2O, 0.2 mmol of Co(NO3)2·6H2O, 0.2 mmol of Ni(NO3)2·6H2O, 0.2 mmol of Zn(NO3)2·3H2O and 1.5 mmol of citric acid were dissolved in 20 mL of a solution with a mass ratio of water to ethanol of 1:1, and ultrasonicated for 5 min to form solution A.

[0072] Weigh 0.7 mmol of Na2MoO4·2H2O and dissolve it in 15 mL of deionized water. Ultrasonicate for 5 min to form solution B.

[0073] Solution B was slowly added to solution A to form a precursor solution, and ultrasonicated for 5 minutes. The treated carbon cloth substrate was then placed in a 50 mL polytetrafluoroethylene liner, and the stirred precursor solution was then added to the liner and sealed. Then it was transferred to a stainless steel autoclave and kept at 160°C for 24 hours. Then it was naturally cooled to room temperature, and the carbon cloth loaded with the catalyst was rinsed with deionized water and ethanol, and finally dried in a vacuum drying oven overnight.

[0074] (2) A typical three-electrode system was used to perform linear sweep voltammetry tests on a Chenhua electrochemical workstation; x The nickel foam substrate was used as the working electrode, the platinum electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and 1 M KOH and 0.1 M glycerol were used as the electrolyte. The test results showed that when the current density reached 10 mA cm -2 When FeCoNiZnMoO x The potential was 1.36 V vs. RHE.

[0075] Example 4

[0076] (1)FeMnNiCuMoO x Synthesis of:

[0077] FeMnNiCuMoO was prepared by a one-step hydrothermal method. x The specific preparation process is as follows:

[0078] 0.1 mmol of Fe(NO3)3·9H2O, 0.2 mmol of Mn(NO3)2·5H2O, 0.2 mmol of Ni(NO3)2·6H2O, 0.2 mmol of Cu(NO3)2·3H2O and 1.5 mmol of citric acid were dissolved in 20 mL of a solution with a mass ratio of water to ethanol of 1:1, and ultrasonicated for 5 min to form solution A.

[0079] Weigh 0.7 mmol of Na2MoO4·2H2O and dissolve it in 15 mL of deionized water. Ultrasonicate for 5 min to form solution B.

[0080] Solution B was slowly added to solution A to form a precursor solution, and ultrasonicated for 5 minutes. The treated nickel foam substrate was then placed in a 50 mL polytetrafluoroethylene liner, and the stirred precursor solution was then added to the liner and sealed. Then it was transferred to a stainless steel autoclave and kept at 160°C for 24 hours. Then it was naturally cooled to room temperature, and the nickel foam loaded with the catalyst was rinsed with deionized water and ethanol, and finally dried in a vacuum drying oven overnight.

[0081] (2) A typical three-electrode system was used to perform linear sweep voltammetry tests on a Chenhua electrochemical workstation; x The nickel foam substrate was used as the working electrode, the platinum electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and 1M KOH and 0.1M glycerol were used as the electrolyte. The test results showed that when the current density reached 10mAcm -2 When FeMnNiCuMoO x The potential was 1.38 V vs. RHE.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that FeCoNiCuMoO x During the preparation process, the molar ratio of all metals is the same, that is, 0.2 mmol, as follows: 0.2 mmol Fe(NO3)3·9H2O, 0.2 mmol Co(NO3)2·6H2O, 0.2 mmol Ni(NO3)2·6H2O, 0.2 mmol Cu(NO3)2·3H2O and 1.5 mmol citric acid are dissolved in 20 mL of a solution with a mass ratio of water to ethanol of 1:1, and ultrasonicated for 5 min to form solution A.

[0084] Then weigh 0.2 mmol of Na2MoO4·2H2O and dissolve it in 15 mL of deionized water, and ultrasonicate for 5 min to form solution B.

[0085] The other preparation steps are the same as those in Example 1.

[0086] The change in the Fe content will adjust the distribution and properties of active sites on the surface of the material. Example 1 Reducing the Fe content makes the types and number of active sites more reasonable, thereby improving the catalytic selectivity and activity of the material for a specific reaction, making it exhibit better performance in the catalytic reaction.

[0087] Comparative Example 2

[0088] The difference from Example 1 is that FeCoNiCuMoO x During the preparation process, 0.1 mmol of citric acid was added to solution A, and the other preparation steps were the same as those in Example 1.

[0089] Citric acid is a multidentate ligand that can react with a variety of metal ions. When the citric acid content in Example 1 is high, it can form more stable complexes with metal ions such as Fe, Co, Ni, Cu, and Mo. These complexes can more evenly distribute metal ions in the subsequent reaction process, promote the synergistic effect between the metal ions, and make the material have better electrochemical properties, thereby showing a lower potential in the LSV test.

[0090] Comparative Example 3

[0091] The difference from Example 1 is that FeCoNiCuMoO x During the preparation process, the hydrothermal reaction temperature was maintained at 180° C. for 24 hours, and the other preparation steps were the same as those in Example 1.

[0092] At a lower hydrothermal temperature (160°C), the movement and diffusion of atoms are relatively slow, which is conducive to the formation of a more uniform and more disordered amorphous structure. The interaction between atoms in this structure is more stable, with fewer defects and stresses, and can provide a more favorable electron transmission path, thereby showing a lower potential and better electrochemical performance in the LSV test. Example 1 The hydrothermal condition of 160°C may cause the material to form a more suitable pore structure and a larger specific surface area. The appropriate pore structure is conducive to the penetration of the electrolyte and the transport of ions, increases the contact area between the electrode and the electrolyte, and improves the efficiency of the electrochemical reaction. A larger specific surface area can provide more active sites, making the reaction easier to proceed, thereby reducing the potential and improving the overall performance.

[0093] It can be seen from the above embodiments and comparative examples that different ratios of raw salts will cause uneven distribution of different elements in the system, and some elements will be locally enriched to form special atomic clusters or short-range ordered structures. This can produce more types of active sites. Different ratios of elements will cause changes in interatomic bond lengths and bond angles, and produce more lattice defects, such as vacancies, interstitial atoms, etc. These defects can act as ion or electron transport channels, improving ion conductivity or electron mobility.

[0094] 2. Properties of High Entropy Molybdenum-Based Oxides

[0095] X-ray diffraction (XRD) was performed on a Philips X'Pert Pro Super diffractometer with Cu Kα radiation as the X-ray source. Figure 1 is the XRD spectra of Examples 1-4 of the present invention; Figure 1 It can be seen that there is no obvious diffraction peak at 5-80°, but when the range is adjusted to 5-40°, a weak peak can be seen. This is because the sample contains multiple phases, and the diffraction peaks of each phase overlap each other. Changes in the phase content will change the peak fluctuations.

[0096] Transmission electron microscopy (TEM) was performed using a JEM-2100F field emission electron microscope at an accelerating voltage of 200 kV; high-resolution transmission electron microscopy (HRTEM) was performed on a ThermoFischer Talos F200X instrument; high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and corresponding elemental mapping analysis were performed. Figure 2 TEM and SEM of Example 1 of the present invention. Figure 2 From the TEM in the figure, we can see that the catalyst surface is flaky and porous; the scale in the SEM is larger and the flaky structure is more obvious.

[0097] from Figure 1 There is no diffraction peak other than the foam metal in the XRD. Figure 2 There are no lattice fringes in the high-resolution electron microscope, which indicates that the high-entropy molybdenum-based oxide prepared by the present invention has an amorphous structure.

[0098] FeCoNiCuMoO x LSV test with and without glycerol in electrolyte. Linear sweep voltammetry test was performed on a Chenhua electrochemical workstation using a typical three-electrode system; a nickel foam substrate loaded with high entropy metal molybdate was used as the working electrode, a platinum electrode was used as the counter electrode, a Hg / HgO electrode was used as the reference electrode, and 1M KOH and 0.1M glycerol were used as the electrolyte. Figure 3 This is a property comparison diagram of embodiment 1 of the present invention in 0.1M glycerol (1M KOH) electrolyte and 1M KOH electrolyte; Figure 3 It can be seen that the current density is greater in glycerol. This is because high entropy molybdates produce larger lattice distortions due to the mixture of multiple metal elements. This distortion can change the electronic structure of the material, leading to an increase in the electronic state density, which is beneficial to the transmission and transfer of electrons, and is manifested as an increase in current density in the LSV test.

[0099] Figure 4 LSV curves of embodiments 1-4 of the present invention in 1M KOH and 0.1M glycerol (1M KOH) electrolyte. Figure 4 It can be seen that the main product is FeCoNiCuMoO x , compared with other products in the electrolyte with and without glycerol, it can be seen that the main product has a higher current density, a lower starting potential, and a better ability to interfere with electrochemical activity. This is because the electrode material has a highly efficient catalytic effect on the electrochemical reaction, which can reduce the activation energy of the reaction and make the reaction easier to proceed. This will result in a significant current being generated at a lower potential, that is, the starting potential is reduced. At the same time, efficient catalysis can also accelerate the reaction rate, increase the substances participating in the reaction per unit time, and thus produce a higher product current density.

[0100] Based on the above analysis, it can be seen that the amorphous state of high-entropy molybdenum-based oxides can provide abundant and relatively evenly distributed active sites to ensure efficient electrochemical reactions; the electrodes made of amorphous high-entropy molybdenum-based oxides and carriers have high activity and good conductivity; the oxidation reaction of small molecules such as glycerol replaces the OER process in water electrolysis, which can achieve efficient hydrogen production and improve the working efficiency of water electrolysis; using glycerol as the electrolyte, the current density is stable and the performance is stable. At the same time, glycerol can generate a variety of value-added chemical products such as formic acid, glyceric acid, etc. through electro-oxidation, thereby realizing the electrochemical value-added of glycerol.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high entropy molybdenum-based oxide, characterized in that: The chemical formula of the high entropy molybdenum-based oxide is MFeMoO x , wherein 2≤x≤4, M is any three or more elements of V, Cr, Mn, Co, Ni and Cu, the total molar ratio of M to Fe is the same as the molar ratio of Mo, the molar ratio of each element in M ​​is the same, and the high entropy molybdenum-based oxide is an amorphous structure.

2. The high entropy molybdenum-based oxide according to claim 1, characterized in that The M is any three of V, Cr, Mn, Co, Ni and Cu.

3. The high entropy molybdenum-based oxide according to claim 1, characterized in that The high entropy molybdenum-based oxide is FeCoNiCuMoO x 、FeCoVCuMoO x 、FeCoNiZnMoO x and FeMnNiCuMoO x One of the following, where 2≤x≤4; Preferably, the molar ratio of Fe to any three elements of V, Cr, Mn, Co, Ni and Cu in M ​​is 1:2:2:

2.

4. A method for preparing a high entropy molybdenum-based oxide according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) adding M metal salt, iron salt and citric acid into a solvent to form a mixed solution; adding an aqueous solution of a molybdenum salt to the mixed solution to form a precursor solution; (2) After the carrier is mixed with the precursor solution, it is sealed and subjected to a hydrothermal reaction to obtain a carrier loaded with a high-entropy molybdenum-based oxide.

5. The method for preparing a high entropy molybdenum-based oxide according to claim 4, characterized in that: In step (1), the M metal salt is any three or more of soluble salts of V, Cr, Mn, Co, Ni and Cu; The iron salt is one of ferric nitrate, ferric sulfate and ferric chloride; The total molar ratio of the iron salt and the M metal salt to the molar ratio of citric acid is (0.5-1.0): (1.0-2.0); The solvent is a mixed solution of water and ethanol; The mixing mass ratio of water to ethanol is 1:(1-3); The concentration of the citric acid is 0.05-0.1 mol·L -1 .

6. The method for preparing a high entropy molybdenum-based oxide according to claim 4, characterized in that: In step (1), the molybdenum salt is one or more of Na2MoO4·2H2O, molybdenum nitrate, molybdenum chloride and molybdenum sulfate; The concentration of the molybdenum salt aqueous solution is 0.04-0.06 mol·L -1 .

7. The method for preparing a high entropy molybdenum-based oxide according to claim 4, characterized in that: In step (2), the carrier is one of carbon cloth, carbon fiber, foam copper, stainless steel mesh and foam nickel; The temperature of the hydrothermal reaction is 140-160° C. and the time is 20-25 hours.

8. Use of the high entropy molybdenum-based oxide according to any one of claims 1 to 3 in glycerol electrooxidation, characterized in that: The concentration of glycerol in the glycerol electrooxidation is 0.05-0.15 mol·L -1 .

9. A method for electro-oxidation of glycerol, characterized in that: The electro-oxidation is carried out using the high entropy molybdenum-based oxide described in any one of claims 1 to 3 as a working electrode, a platinum electrode as a counter electrode, a Hg / HgO electrode as a reference electrode, and KOH and glycerol as electrolytes.

10. A composite electrode, characterized in that: The invention comprises a conductive substrate and the high entropy molybdenum-based oxide according to any one of claims 1 to 3 loaded on the surface of the conductive substrate.

Citation Information

Patent Citations

  • Nickel sulfide / nickel oxide electrode and preparation method and application thereof

    CN117070989A